Estudo do aproveitamento dos resíduos da construção civil na substituição dos agregados em blocos de concreto - Gomes, Wesley Pinheiro (Universidade Federal do Tocantins, 2022)
The concern with the environment has increased every day and has motivated research on the use of Waste in Civil Construction (RCC), as this consumes a large part of non-renewable resources such as aggregates in its production. The study sought an evaluation of the mechanical and physical properties of concrete blocks with the replacement of conventional aggregates by RCC. The present work deals with the reuse of aggregates from civil construction, taking advantage of these in the replacement of aggregates commonly used in the manufacture of concrete blocks. This material describes the entire procedure for capturing the material at the plant, treating it to be able to use it, making the structural masonry blocks in a block factory in the city of Palmas, Tocantins, using lines with 5%, 10% and 15% replacement of the usual aggregates, sand and crushed dust by civil construction waste that went through a 4.8mm sieve, which were analyzed based on tests such as workability, absorption and compressive strength. The response surface analysis showed that the curing time variable influences more on the strength of the blocks than the percentage of residues used to replace the conventional aggregate, the results also show that the replacement of conventional aggregates by RCC in concrete blocks is a sustainable and technical alternative for blocks without structural function, since the analyzed traits in this research did not reach the minimum value for structural function of 3.00 MPa.